Controlled human infection with RSV: The opportunities of experimental challenge. Issue 3 (11th January 2017) - Habibi, Maximillian S.; Chiu, Christopher
Highlights: Experimental human RSV infection bridges pre-clinical models and clinical trials. RSV challenge allows early proof-of-concept efficacy assessment. Sampling of RSV-infected lung permits novel insights into mucosal immunity. Understanding of respiratory mucosal immune correlates directs vaccine development. Cooperation between academics, industry and funders is needed for sustainability. Abstract: Despite the recent explosion in RSV vaccine development, there remain substantial hurdles to overcome before licensing of effective vaccines will allow widespread use, particularly in high-risk populations. Incomplete understanding of mechanisms and correlates of protection against RSV mean that, for the time being, successful RSV vaccines must directly demonstrate efficacy, which necessitates large and costly clinical trials in naturally infected patients. To mitigate the risks inherent in progressing to these late-stage trials, experimental human RSV infection studies have recently been re-established, representing the interface between pre-clinical models and observational studies of patients. Not only can they be used for early proof-of-concept clinical trials to test vaccine efficacy, but human challenge studies also offer the potential to better understand protective immunity against RSV infection to improve vaccine design and delivery. In the past, controlled human infection studies with RSV have been instrumental in elucidating the influence of factors such as route of infection and type of inoculum on the course of disease. Recently, efficacy trials of novel RSV antiviral drugs have also been successfully undertaken. Now, with advances in technology, detailed investigations of human mucosal immunity in the RSV-infected airway are possible. These have indicated defects in RSV-induced humoral and CD8+ T cell immunity that may contribute to the recurrent symptomatic infection that occurs throughout life and should be circumvented by optimal vaccines. Here, we discuss the insights derived from RSV human challenge models; the major impediments to their more widespread uptake; and their potential benefit in accelerating vaccine development, including future directions to further enhance the relevance of these models to at-risk patient populations.